2003
DOI: 10.1001/archpsyc.60.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder and the Incidence of Nicotine, Alcohol, and Other Drug Disorders in Persons Who Have Experienced Trauma

Abstract: The findings do not support the hypothesis that exposure to traumatic events per se increases the risk for substance use disorders. A modestly elevated risk for nicotine dependence might be an exception. Posttraumatic stress disorder might be a causal risk factor for nicotine and drug use disorders or, alternatively, the co-occurrence of PTSD and these disorders might be influenced by shared risk factors other than traumatic exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
398
7
17

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 524 publications
(459 citation statements)
references
References 41 publications
32
398
7
17
Order By: Relevance
“…Recent studies have found important linkages between smoking and certain anxiety disorders (Feldner, Babson, & Zvolensky, 2007a;Morissette, Tull, Gulliver, Kamholz, & Zimering, 2007;Patton, Carlin, Coffey, Wolfe, Hibbert, & Bowes, 1998; Zvolensky, Feldner, LeenFeldner, & McLeish, 2005 (Beckham et al, 1995;Breslau et al, 2003;Buckley et al, 2004;Feldner et al, 2007a). Recent controlled work supports the contention that PTSD is associated with earlier relapse compared to persons with no psychopathology (Zvolensky, Gibson et al, in press).…”
Section: Nih Public Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have found important linkages between smoking and certain anxiety disorders (Feldner, Babson, & Zvolensky, 2007a;Morissette, Tull, Gulliver, Kamholz, & Zimering, 2007;Patton, Carlin, Coffey, Wolfe, Hibbert, & Bowes, 1998; Zvolensky, Feldner, LeenFeldner, & McLeish, 2005 (Beckham et al, 1995;Breslau et al, 2003;Buckley et al, 2004;Feldner et al, 2007a). Recent controlled work supports the contention that PTSD is associated with earlier relapse compared to persons with no psychopathology (Zvolensky, Gibson et al, in press).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Similarly, smoking rates are significantly greater among persons with, compared to those without, PTSD (Acierno et al, 2000;Acierno, Kilpatrick, Resnick, Saunders, & Best, 1996;Beckham et al, 1995;Buckley, Mozley, Bedard, Dewulf, & Greif, 2004). Investigations also have found that exposure to traumatic life events, particularly for those individuals with a PTSD diagnosis, is associated with an increase in smoking behavior (e.g., increasing the amount of cigarettes smoked per day; Breslau, Davis, & Schultz, 2003;Joseph, Yule, Williams, & Hodgkinson, 1993;Koenen et al, 2005;Perkonigg, Kessler, Storz, & Wittchen, 2000). Although less is empirically known about the role of PTSD in cessation success per se, scholars have suggested that this clinical condition may (theoretically) be associated with poor cessation outcome (Beckham et al, 1995;Breslau et al, 2003;Buckley et al, 2004;Feldner et al, 2007a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that ongoing exposure to stress or traumatic abuse increases susceptibility to substance abuse (Breslau, Davis, & Schultz, 2003;Piazza & Le Moal, 1996;Simpson & Miller, 2002). One explanation is that the anxiety-reducing effects of substances, which alter the brain's behavioral inhibition system (Walker et al, 1991) and affect reward systems of the brain (e.g.…”
Section: Violence Exposure Mediates the Relation Between Callous-unemmentioning
confidence: 99%
“…Associations between PTSD and substance use disorders have been reported in several studies (Kandel et al, 1997;Breslau et al, 1994Breslau et al, , 2003Breslau et al, , 1991. US data show that 60% of help-seeking PTSD patients smoke cigarettes, compared to 23% of the general population, and also that patients with PTSD are more likely to be heavy smokers (Beckham, 1999).…”
Section: Introductionmentioning
confidence: 95%